Estudio de factibilidad para la creacion de una empresa comercializadora de souvenirs de la facultad de Ciencias Empresariales, canton Quevedo, año 2013 - Zorrilla Ortega, Ingrid Rebeca (2013)
Below are summarized the results as part of this investigation, the same that was intended to carry out a feasibility study for the establishment of a trading company souvenir of the Faculty of Business Sciences, 2013. For this reason it was observed that the main causes that headed to this research were: the lack of a market study for analyzing the supply and demand for the product above the lack of a technical study to determine the legal structure, organizational and physical souvenir of a marketer that has never been created in the FCE and finally the need for an economic study that reflect financial products admitting the economic viability of the project. As for the market study by the results obtained through the surveys could deduce that 100% of respondents have never before witnessed the creation of marketing necessary to provide these products in the FCE, so that the observed short supply and that is a very important plus point for project creation. 53% of respondents felt favorably to implement the marketing of souvenirs, so this percentage shows the demand for the product. 88% of respondents agree that it is believed a company of souvenirs for the purpose of strengthening the institutional identity. 88% of respondents would like the company to offer its range of products such as souvenirs, hats, shirts, keychains, pins, bags, hats, pens, souvenirs grade, glasses, wallets and piggy agendas. 31% of respondents agree purchase souvenirs at prices ranging from $ 16 to $ 21, while 27% would like the products on the market to a value of $ 1 and $ 5. The majority 91% of respondents indicated that the most suitable place to run trading company souvenir is near the school. Initial investment, funding sources, office equipment, furniture and fixtures, administrative costs, utilities, materials, in order to identify the profitability of the project an economic-financial study, in which the following items formed an essential part developed office, and office supplies, sales expenses, administrative expenses, projected costs 5 years sales, profit and loss statement, projected cash flow, depreciation, cost benefit ratio and profitability indicators. The results of the economic study shows that the net income during the first year of sales trading company souvenir is $ 68,002.25 while the cost benefit ratio is $ 1.29 per every dollar of investment so it can be evidenced that the project is profitable. The project investment is estimated at the amount of $ 13,809.81 so it shall be recovered in a time of 3 years, 10 months and 2 days, besides the internal rate of return shows a 84% feasibility, indicating that the creation of trading company souvenir is feasible.